Influence of the weed competition on yield of onion bulbs - Garcia, Danton Camacho; Barni, Valmor; Storck, Lindolfo (Pesquisa Agropecuaria Brasileira, 1994)
The objective of this research was to evaluate the weed competition effects on onion bulb yields. Three field experiments were conducted in Rio Grande, RS, Brazil, during the 1982/83, 1983/84 and 1984/85 growing seasons. The experimental design was in randomized blocks with four replications, and the treatments were different competition periods to which onion plants were submitted. The results indicated that the threshold occurred from 61 to 74 days after transplanting. The crop must be kept weed free at least at this period in order to maximize bulb yields. Yield reduction estimates ranged between 4.45 and 70.5% according to the growing season.